African poverty at the millenium : causes, complexities, and challenges - White, Howard; Killick, Tony. (Washington, D.C. : World Bank, 2001)
The book explores the complex nature of poverty in the region, identifies its political and social causes, and assesses the impact of recent economic growth on the welfare of poor people.
Includes bibliographical references.
osa 05/09/2016
Loans
Keywords: Poverty- Africa; Africa - Economic conditions; African poverty; Africa